Предмет: Математика,
автор: lobanovasnezanna
Наити значение выражении (3x+7)-4x при x-6
petrpetranybaev:
ээто?
Ответы
Автор ответа:
0
Ответ:
Выражение
(3x + 7) - 4x(3x+7)−4x
при х = -6 равно:
\begin{gathered}(3 \times ( - 6) + 7) - 4 \times ( - 6) = \\ ( - 18 + 7) - ( - 24) = \\ - 11 + 24 = 13\end{gathered}
(3×(−6)+7)−4×(−6)=
(−18+7)−(−24)=
−11+24=13
Похожие вопросы
Предмет: Окружающий мир,
автор: Саимат2007
Предмет: Русский язык,
автор: bogomolovasvet1
Предмет: Русский язык,
автор: Настябелка11рак
Предмет: Окружающий мир,
автор: Аноним
Предмет: Русский язык,
автор: Scholnik2220